Paciente masculino recién nacido con síndrome de distrés respiratorio. - Itaz Bravo, María Mayelhi (2021)
Neonatal RDS occurs in babies whose lungs have not yet fully developed. The disease is mainly caused by a lack of a slippery, protective substance called surfactant. Most cases of RDS are seen in babies born before 37 to 39 weeks. The less developed the lungs, the greater the chance of developing neonatal respiratory distress syndrome after birth. Other factors may be Diabetes in the mother, Cesarean delivery, Delivery problems that reduce circulation to the baby, Multiple pregnancy (twins or more) and Rapid labor. Symptoms may include Cyanosis, Apnea, Decreased urinary output, Nasal flaring, Rapid breathing, Shallow breathing, Difficulty breathing, hoarse sounds while breathing, and retraction of the chest muscles. Chest X-ray and CBC exam Treatment such as using ventilator-assisted ventilation can save the lives of some babies.